Solve the equation ,
for positive integers x and y .
Answers
Answer:
Original equation:
y3=x3+8∗x2−6∗x+8 -- (1)
Subtract equation-(1) by (x−1)3 on both sides,
We have,
y3−(x−1)3=(x3+8∗x2−6∗x+8)−(x−1)3
=5∗x2−9∗x+7 -- (2)
Consider the following quadratic equation (from RHS of equation-(2)) ,
5∗x2−9∗x+7=0
Its discriminant is 92−4∗5∗7=−59, which is less than zero. Now, from the theory of quadratic equations, we know that negative discriminant indicates that the above quadratic expression is positive for every real value of x . Hence,
5∗x2−9∗x+7>0 for every real x
From equation - (2),
=>y3−(x−1)3>0 for every real x
=>(x+1)<y -- (3)
Similarly, subtracting both sides of equation-(1) by (x+3)3 fetches the following:
(x+3)3−y3=(x+3)3−(x3+8∗x2−6∗x+8)
=x2+33∗x+19 -- (4)
x2+33∗x+19 has a positive derivative w.r.t x for x>0 i.e, (x+33). Hence, it is a monotonically increasing expression for x>0 . At x=0 , the value of x2+33∗x+19 is 19 ( >0 ). Hence, x2+33∗x+19>0 for x>0 and from equation-(4),
(x+3)3−y3>0
=>(x+3)>y -- (5)
From equations (3) and (5),
(x+1)<y<(x+3)
As we seek a positive integral solution,
y must be equal to (x+2).
Now substituting y=(x+2) in equation-(1), we get
2∗x2−18∗x=0
Two solutions:
- x=0 and y=2
- x=9 and y=11.
Solution:-Can be solved by simple.method
given that:-y^3=x^3+8x^2+8
here analysing we get
(x+2)^3+2x^2-18x=x^3+8+6x^2+12x+2x^2-18x=x^3+8x^2-6x+8
so,
y^3=x^3+8x^2+8=(x+2)^3+2x^2-18x
y^3+0=(x+2)^3+2x^2-18x
comparing both side we get
y^3=(x+2)^3......i)
and,0=2x^2-18x
2x^2=18x........ii)
x(2x-18)=0
x=0,x=9
now it said that,x is positive only,
so,ignore x=0
because 0 is neither positive nor negative
hence,x=9
putting this value in i) we get
y^3=(11)^3
y=11
hence,x=9 and y=11
{hope it helps}